2009
DOI: 10.1002/hyp.7259
|View full text |Cite
|
Sign up to set email alerts
|

Integration of remote sensing and GIS for modelling flash floods in Wadi Hudain catchment, Egypt

Abstract: Abstract:This paper presents a new approach to modelling flash floods in dryland catchments by integrating remote sensing and digital elevation model (DEM) data in a geographical information system (GIS). The spectral reflectance of channels affected by recent flash floods exhibit a marked increase, due to the deposition of fine sediments in these channels as the flood recedes. This allows the parts of a catchment that have been affected by a recent flood event to be discriminated from unaffected parts, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 28 publications
0
46
0
Order By: Relevance
“…According to Gheith and Sultan (2002), only 3-7 % of the precipitation reached the watershed outlets for the Red Sea mountains (Eastern desert) in Egypt. El Bastawesi et al (2009) found for Wadi Hudain (Easter Desert) in Egypt that most of the runoff infiltrates into the alluvium during its transmission through the channel.…”
Section: Forecasting Runoff and Dischargementioning
confidence: 99%
“…According to Gheith and Sultan (2002), only 3-7 % of the precipitation reached the watershed outlets for the Red Sea mountains (Eastern desert) in Egypt. El Bastawesi et al (2009) found for Wadi Hudain (Easter Desert) in Egypt that most of the runoff infiltrates into the alluvium during its transmission through the channel.…”
Section: Forecasting Runoff and Dischargementioning
confidence: 99%
“…Therefore, the mapping of surface drainage channels and catchment outlets can be derived with reasonable accuracy using the space-born DEM such as the Shuttle Radar Topography Mission (SRTM) DEM (e.g. Ghoneim and El-Baz, 2007;El Bastawesy et al, 2009). However, the accuracy and reliability of the hydrographic parameters simulation using DEM are known to be influenced by source, resolution and processing algorithms (Zhang and Montgomery, 1994;Wolock and McCabe, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The catchments are ungauged, and this complicates the understanding of their hydrological processes. Remote sensing data can be used to derive relevant hydrological parameters such as the location of active channels and flood deposits, thus indicating the maximum inundation of channels and the most downstream points reached by the flows (El Bastawesy et al, 2009). The recent release of the MSS, TM and ETM satellite images archive of the United Sates Geological Survey (USGS web) for free download allows the close assessment of the active channels of different flash flood events in these dry land catchments.…”
Section: Hydrologymentioning
confidence: 99%